Taṣmīm Qāmūsi at-Tiknūlūjiyā al-Mu‘āṣir (Indūnīsiyā-‘Arabī) li Iṡrā'i Mufrādāt Ladā Qismi Tiknūlūjiyā al-Ma‘lūmāt bi Jāmi‘ati Dārissalām Gontor - ACHMAD FAROUQ ABDULLAH; Khadijjah Sammah; Fitri Setyo Rini (Lisanudhad: Jurnal Bahasa, Pembelajaran, dan Sastra Arab, 2024)
University of Darussalam Gontor, as one of the higher education institutions that places significant emphasis on the development of the Arabic language, considering one of its visions is to become a center for the study of the Quranic language and the Arabic language, prioritizes the teaching of Arabic in all its faculties. Every student is required to take a comprehensive examination in both languages, and university theses must be written in the official language. Therefore, the Information Technology program is an integral part of the university that must adhere to these requirements. However, in practice, students do not write their theses in Arabic due to the limited vocabulary and terminology in the field of Information Technology in the Arabic language, which remains challenging to find. As a result, this research aims to compile a contemporary Information Technology dictionary that aligns with the needs of the Information Technology program at University of Darussalam Gontor and to measure the effectiveness of the contemporary Information Technology dictionary design in enriching the vocabulary of Information Technology students at University of Darussalam Gontor. The research method employed in this study is the Research and Development (R&D) method with a quantitative approach using the ADDIE framework. The results of this research indicate that the contemporary Information Technology dictionary has had a positive impact on enriching students' vocabulary, as evidenced by the paired t-test. The data obtained show values below 0.05, which means that the null hypothesis is rejected, and the alternative hypothesis is accepted. Keywords: Contemporary Technology Dictionary, Vocabulary, Terms, Information Technology, Arabic Teaching